Different drying techniques effect on the bioactive properties of rose petals - Ahmad Mohammad Salamatullah; Mohammed Asif Ahmed; Khizar Hayat; Fohad Mabood Husain; Shaista Arzoo; Abdulhakeem Alzahrani; Asdaf Alotaibi; Heba Khalil Alyahya; Syed Rizwan Ahmad (Journal of King Saud University: Science, 2024)
This study explored the effect of different drying methods (sun, shade, oven) on the total polyphenol content (TPC) using the Folin–Ciocalteu (FC) procedure, total flavonoid content (TFC) using the AlCl3 colorimetric method, volatile organic compounds using GC/MS and the antioxidant properties of the rose petals using the protocol of DPPH assy. The results demonstrated that the drying methods had a significant impact and the highest TPC (34.24 mg gallic acid equivalent (GAE)/ g fresh weight (FW)) and TFC (5.56 mg catechin equivalent (CE)/g FW) were obtained for the oven-dried sample. While, the fresh sample exhibited the lowest TPC (15.6 mg GAE/g FW) and TFC (3.83 mg CE/g FW), respectively. Similarly, the oven-dried sample showed the highest DPPH scavenging activity (60.30 %) and reducing power (absorbance 1.138) among all the samples. Fresh rose sample GC–MS analysis revealed that the there are two major compounds heptacosane 64.56 % and citronellyl propionate 28.35 %. Pentadecyl 2-phenylethyl ester oxalic acid was the second dominant compound in sun and oven-dried rose samples, 18.5 % and 14.79 % respectively.